2018
DOI: 10.3233/jad-170509
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510

Abstract: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 55 publications
8
68
0
Order By: Relevance
“…From the 1.5 h dynamic scans, we found that the radiotracer uptakes were mainly located in the brain regions such as the cortex, hippocampus, and striatum, which is comparable with previous findings [23], further confirming the tau-specific binding ability of 18 F-PM-PBB3. The steady-state for each brain region from the TAC was found roughly 40 min after the tracer injection, which also matches the results of studies using C-11 labeled PBB3 [17,31]. The tracer kinetic distribution on the rTg4510 mouse brain regions is slower than 18 F-THK523, which reached the plateau roughly 20-30 min post tracer injection [11].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…From the 1.5 h dynamic scans, we found that the radiotracer uptakes were mainly located in the brain regions such as the cortex, hippocampus, and striatum, which is comparable with previous findings [23], further confirming the tau-specific binding ability of 18 F-PM-PBB3. The steady-state for each brain region from the TAC was found roughly 40 min after the tracer injection, which also matches the results of studies using C-11 labeled PBB3 [17,31]. The tracer kinetic distribution on the rTg4510 mouse brain regions is slower than 18 F-THK523, which reached the plateau roughly 20-30 min post tracer injection [11].…”
Section: Discussionsupporting
confidence: 81%
“…Afterward, another advanced radioligand, 18 F-THK5351, was developed with much lower white matter binding and higher binding specificity only focusing on the abnormal tau-associated regions [14,15]. However, the dominant binding was delineated from 18 F-THK5351 in the brain regions such as the basal ganglia, thalamus, and brainstem and this tracer's off-target binding to monoamine oxidase-B (MAO-B) has been verified [16,17]. Like 18 F-THK5351, 18 F-Flotaucipir has also demonstrated superior binding properties specific to tau proteins [18][19][20]; however, this tracer also has the off-targeting issue, and it has been further confirmed that this non-specific binding could be derived from monoamine oxidase-A (MAO-A) or MAO-B [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Speculatively, this could indicate different predictive capability of TSPO µPET depending on whether tau or amyloid-β accumulation is the primary driver of microgliosis. Regarding tau mouse models, our observation of higher tau accumulation in mice with early microglial activation is in line with findings of associated tau and neuroinflammation in the forebrain of rTg4510 tau mice [32]. Our data also fit with the observations of attenuated NFT accumulation, reduced neuronal degeneration, and averted cognitive deterioration after pharmacological ablation of senescent microglial and astroglial cells in PS19 mice [33], as well as fitting with the increased tau pathology occurring along with NLRP3 inflammasome activation [7].…”
Section: Discussionsupporting
confidence: 89%
“…P301S and P301L lines (transgenic for a human 4 repeat tau isoform) [6,[52][53][54], which have become important tools to study the mechanisms of abnormal tau aggregation and deposition in FTD (4 repeat tau) [61] and AD (3 and 4 repeat tau) [25, 33,41]. In the P301L 4 (Thy 1.2, pR5 line) [11,18], P301L (CaMKIIa) [23,43,62] and P301L (tetO) [14] mouse models, tau deposits begin forming before 3 months-of-age in neurons in the entorhinal cortex, hippocampus and later in the cortex, and amygdala; with neuroinflammation and impaired memory functions in hippocampus-and amygdala-dependent tasks manifesting at a later stage [49,50,67]. Brain atrophy and white matter changes indicating neurodegeneration were reported in P301L (CaMKIIa) mouse line around 9 months-of-age [16,23,43,62], which was driven by factors additional to human tau overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…In the P301L 4 (Thy 1.2, pR5 line) [11,18], P301L (CaMKIIa) [23,43,62] and P301L (tetO) [14] mouse models, tau deposits begin forming before 3 months-of-age in neurons in the entorhinal cortex, hippocampus and later in the cortex, and amygdala; with neuroinflammation and impaired memory functions in hippocampus-and amygdala-dependent tasks manifesting at a later stage [49,50,67]. Brain atrophy and white matter changes indicating neurodegeneration were reported in P301L (CaMKIIa) mouse line around 9 months-of-age [16,23,43,62], which was driven by factors additional to human tau overexpression. However, unlike in human patients with tauopathies, brain calcifications have not been reported in transgenic mouse models of human disease.…”
Section: Introductionmentioning
confidence: 99%